Hubungan Pendidikan dan Pekerjaan dengan Kecemasan pada Gay, Transgender, LSL Bandar Lampung - Resati Nando Panonsih; Ade Utia Detty; Arif Effendi; Rika Arianofela (ARTERI : Jurnal Ilmu Kesehatan, 2020)
Gay, Transgender, and MSM are group that experiencing detention in their health. This group susceptive of anxiety due to negative response from their environment especially from education and occupation. From the other research, showed that 44% from 277 gay having anxiety disorders. This condition becomes very impotant because the higher of anxiety will impact to their physical and physicological condition.Objective: To determine the relationship between education and occupation with levels of anxiety to the Gay, Transgender, and MSM in Bandar Lampung 2019. Methods: The types of research is an analytic survey with cross-sectional approach. The type of data obtained are primary data. The method of collecting data is by given quesionnaire to get answer from subjects. This research was conducted during November 2019. In this research, the samples taken included all member of Gaya Lentera Muda organization of 35 subjects by total sampling technique. Results: It is known from the results of this research that the subjects (gay, transgender, and msm) mostly have middle of 19 subjects (54,3%), mostly have an occupation of 18 subjects (51,4%),and the subjects with middle education have mild anxiety of 7 subjects (36,8%) and the subjects with an occupation mostly have mild anxiety of 9 subjects (50,0%). Conclusion: The final results showed that there is a meaningful relationship between education and occupation with levels of anxiety to gay, transgender, and MSM in Bandar Lampung 2019 (p-value = -0,547 and p-value = -0,595). Higher the levels of education and if the person has an occupation, levels of anxiety will higher.